War of Independence 1857 and the Peshawar Valley - Turab-ul-Hassan Sargana (JSSH, 2023)
During the War of Independence 1857-58, the areas, including Peshawar, which are now called Khyber Pakhtunkhaw were part of the Punjab Province. When the news of outbreak of war reached at Lahore and Peshawar, the people of Punjab started preparations to rise against the foreign rule. The British had to face many uprisings in the Punjab and the people rose against them at Gugera,